ANTIBACTERIAL ACTIVITY OF ETHANOLIC EXTRACT OF KITOLOD (Hippobroma longiflora) LEAVES AGAINST STREPTOCOCCUS PYOGENES - Tanaja, Grace Isabella; Isbandiati, Endang; Wattimena, Inge (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2022)
Background: Antimicrobial resistance to antibiotics has been emerging as a serious issue in healthcare, hence the need to discover and develop new treatment alternatives. Chemical compunds found in medicinal plants can potentially be used to synthesize new antibiotic agents, one of which is the leaves of kitolod (Hippobroma longiflora). Phytochemical screening of kitolod leaves showed positive results for secondary metabolites presumed to have antibacterial effects. Objectives: The purpose of this study was to examine the antibacterial activity of ethanolic extract of kitolod leaves against Streptococcus pyogenes. Methods: Antibacterial activity of the ethanolic extract of various concentrations (0,25%, 1,75%, 3,25%, 4,75%, 6,25%) were evaluated by broth microdilution method on a 96-well microplate and by streaking on agar plates. Results: Minimium Bactericidal Concentration (MBC) of ethanolic extract of kitolod leaves against Streptococcus pyogenes was 1,75%. Minimum Inhibitory Concentration (MIC) of ethanolic extract of kitolod leaves against Streptococcus pyogenes could not be inferred. Conclusion: Ethanolic extract of kitolod leaves showed antibacterial activities against Streptococcus pyogenes.